Participatory design: how may designers create furniture that allows meaningful place-making - Dolah, Mohd Shahrizal; Rust, Chris (Center for Promoting Ideas, 2017)
This paper has developed design method for furniture designer’s that allow users to express their needs through place making or creation of meaningful office workspaces. We discovered that there were problems in getting the users to explain their ideas through verbal explanations. From there we started to use a participatory design approach with mock-ups to investigate the main methods and to explore design opportunities in developing new office environments. The study revealed, by using role-play with mock-ups directly with the users, allowed the designers to quickly become aware of arising issues without the need to do a potentially time-consuming, normative and tedious observational study. This research approach is primarily leads to new understanding about practice and described as "practice-led" approach to research. This project had investigated, demonstrated and opened the possibility that these approaches could be turned into a practical participatory process toward design in furniture industry practice in Malaysia.